Health Care Providers’ Well-being Indicators are Associated With Their Intention to Leave Their Positions: A Cross-Sectional Study From Saskatchewan, Canada - Tasbeen Akhtar Sheekha MSc; Noelle Rohatinsky PhD; Jacob Albin Korem Alhassan PhD; Dennis Kendel MD; Carmen Levandoski BSN; Jeff Dmytrowich RT; Tenille Lafontaine; Matthew Cardinal; Juan Nicolás Peña-Sánchez PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study aimed to measure the intention to leave and well-being indicators (ie, job satisfaction, burnout, moral distress, risk of depression, and resilience) of health care providers (HCPs) in Saskatchewan, Canada and to explore the association between their intention to leave and well-being indicators and other demographic factors, including gender. A cross-sectional study was conducted among registered nurses (RNs), physicians, and respiratory therapists (RTs) in Saskatchewan between December 2021 and April 2022. An online survey inquired about intentions to leave current positions, well-being indicators, and demographics of HCPs. Logistic regression models explored associations between intention to leave current positions and HCPs’ well-being indicators. Adjusted odd ratios (AORs) and 95% confidence intervals (95% CI) are reported. In total, 1497 HCPs participated; 38.6% considered leaving their positions. Controlling by gender, age group, children at home, redeployment, burnout, and resilience levels, the odds of considering leaving their positions decreased by 0.55 (95% CI = 0.43-0.70) per unit of increase in job satisfaction. HCPs experiencing high moral distress were more likely to consider leaving their positions (AOR = 3.97, 95% CI = 2.93-5.39). RNs were more likely to consider leaving their positions than physicians (AOR = 1.68, 95% CI = 1.13-2.50). Age interacted with gender, and burnout interacted with children at home. The job satisfaction, distress levels, and RN designation predicted HCPs’ intention to leave. We must recognize the dissimilar effect of age on the intention to leave between women and men and the effect of burnout between those with and without children. Strategies to increase retention of HCPs should consider well-being indicators and focus on reducing morally distressing environments and redeployment.